ANALYSIS OF THE LEVEL OF RESPONSIBILITY OF APPLIANCES IN IMPLEMENTING TASKS IN PANGEYA VILLAGE WINOSARI DISTRICT BOALEMO DISTRICT - isfan y. igris; Darman; siske Anani (Journal of Economic, Business, and Administration (JEBA), 2022)
This study aims 1) To carry out the level of responsibility of the apparatus in carrying out tasks in Pangeya Village. And 2) To increase the understanding of the apparatus in carrying out functions in Pangeya Village. The method in this research is qualitative with a descriptive approach. According to Miles and Huberman, the data analysis technique used is the data analysis technique, where the activities in data analysis are data reduction, data display, and conclusion drawing/verification. The results of the study show as follows: 1) Organizational responsibility in Pangeya Village is considered not to be running well because there are still several concepts that are not by the needs, especially in carrying out services to the community. 2) Political responsibility in Pangeya Village is considered to have not formed a decision to implement services due to differences in duties and others. 3) Legal responsibility is carried out in carrying out the task because the policies are adjusted to the responsibility in seeing the existing conditions with the existing policies. 4) Professional responsibility with provisions in carrying out the responsibilities of tasks carried out with existing provisions in improving the quality of existing work in carrying out Pangeya Village services.